2010
DOI: 10.1016/j.addbeh.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, cocaine, and heroin: Craving and use during daily life

Abstract: Background-Relationships among tobacco smoking, tobacco craving, and other drug use and craving may have treatment implications in polydrug-dependent individuals.Methods-We conducted the first ecological momentary assessment (EMA) study to investigate how smoking is related to other drug use and craving during daily life. For up to 20 weeks, 106 methadone-maintained outpatients carried PalmPilots (PDAs). They reported their craving, mood, behaviors, environment, and cigarette-smoking status in 2 to 5 random-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 41 publications
(50 reference statements)
4
79
0
2
Order By: Relevance
“…As reviewed previously, craving is a key feature of both SUDs (O'Brien et al, 1998;Volkow et al, 2006) and PG (Potenza et al, 2003b) that predicts drug use, gambling, and relapse to those behaviors (eg, Epstein et al, 2010). Consistently, commonly practiced and effective treatments for these disorders include components on identifying triggers for craving and on regulation of craving (such as relapse prevention and cognitive-behavioral therapy; Carroll, 2008;Grant et al, 2009).…”
Section: Cocaine Cravings and Gambling Urges H Kober Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed previously, craving is a key feature of both SUDs (O'Brien et al, 1998;Volkow et al, 2006) and PG (Potenza et al, 2003b) that predicts drug use, gambling, and relapse to those behaviors (eg, Epstein et al, 2010). Consistently, commonly practiced and effective treatments for these disorders include components on identifying triggers for craving and on regulation of craving (such as relapse prevention and cognitive-behavioral therapy; Carroll, 2008;Grant et al, 2009).…”
Section: Cocaine Cravings and Gambling Urges H Kober Et Almentioning
confidence: 99%
“…Appetitive and motivational states like drug cravings are central to SUDs, including CD (O'Brien et al, 1998;Volkow et al, 2006) and are associated with drug-taking and relapse (eg, Epstein et al, 2010). Similarly, gambling urges contribute importantly to PG, correlating with problem-gambling severity (Petry et al, 2005) and relapse to gambling (Oei and Gordon, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Un bon nombre d'études suggèrent que la consommation d'alcool, de cocaïne, d'héroïne et de tabac chez les individus dépendants est souvent précédée de craving (Epstein, Marrone, Heishman, Schmittner et Preston, 2010 ;Paliwal, Hyman et Sinha, 2008). De plus, la plupart des études démontrent que plus le niveau de craving est important chez les individus dépendants et abstinents, plus le risque de rechute et le retour à la consommation sont probables, autant lors d'une cure de désintoxication en milieu hospitalier que lors d'un suivi en externe (Sinha, 2011).…”
Section: Implications Dans La Rechute Et Avenues Thérapeutiquesunclassified
“…Previous studies have found an extremely high cigarette smoking prevalence (90% or higher) among IDUs and a positive correlation between patterns of cigarette smoking and drug use (Clarke, Stein, McGarry, & Gogineni, 2001;Epstein, Marrone, Heishman, Schmittner, & Preston, 2010;Marshall et al, 2011;Villanti, German, Sifakis, Flynn, & Holtgrave, 2012). Craving for nicotine might increase craving for drugs, particularly for cocaine (Epstein et al, 2010;Harrell, Montoya, Preston, Juliano, & Gorelick, 2011;Levine et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Craving for nicotine might increase craving for drugs, particularly for cocaine (Epstein et al, 2010;Harrell, Montoya, Preston, Juliano, & Gorelick, 2011;Levine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%